A parametric design of ceramic faced composite armor subject to air weapon threats. Issue 1 (November 2015) - Guo, Y N; Sun, Q
Abstract: By taking into consideration the two categories of military projectile threats to aircraft structures, an optimal layer configuration of ceramic faced composite armor was designed in this paper. Using numerical simulations and the same layer arrangement of ceramic, UHMWPE, and carbon fiber laminates, a parametric finite element model using LS-DYNA code was built. Several thickness combinations were analyzed in order to determine the final lightest configuration that is capable of supporting a high-speed impact load and HEI blast wave load, which implements a high anti-penetration design for aircraft armor. This configuration can be used to improve the anti-impact ability of aircraft structures as well as achieve a structure/function integration design that considers a lighter weight.